2015
DOI: 10.1142/s1758825115500799
|View full text |Cite
|
Sign up to set email alerts
|

Induced Damping on Vibrating Circular Plates Submerged in Still Fluid

Abstract: Received RevisedWhen a structure vibrates immersed in a fluid it is known that the dynamic properties of the system are modified. The surrounding fluid will, in general, contributes to the inertia, the rigidity and the damping coefficient of the coupled fluid-structure system. For light structures, like spacecraft antennas, even when the fluid is air the contribution to the dynamic properties can be important. For not so light structures the ratio of the equivalent fluid/structure mass and rigidity can be very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It must be said that the case studied by Kwak is not exactly the same as the one considered here because the rectangular plate is situated in an aperture of an infinite rigid plane wall in contact with water and not fully filled submerged in water as in the present case. Furthermore, one can observe a great reduction in frequency in the wet case (with water) with respect to the vacuum case, and this reduction is higher, the lower the value of the mode considered, see Gascón-Pérez et al [2015]. presents an oscillating variation with the wave number k , reaching a maximum for a certain value of k and decreasing to a zero value for high values of k , so this fluid mass coefficient is analogous to a transfer function relating the fluid pressure jump and the deformation of the membrane.…”
Section: Resultsmentioning
confidence: 97%
“…It must be said that the case studied by Kwak is not exactly the same as the one considered here because the rectangular plate is situated in an aperture of an infinite rigid plane wall in contact with water and not fully filled submerged in water as in the present case. Furthermore, one can observe a great reduction in frequency in the wet case (with water) with respect to the vacuum case, and this reduction is higher, the lower the value of the mode considered, see Gascón-Pérez et al [2015]. presents an oscillating variation with the wave number k , reaching a maximum for a certain value of k and decreasing to a zero value for high values of k , so this fluid mass coefficient is analogous to a transfer function relating the fluid pressure jump and the deformation of the membrane.…”
Section: Resultsmentioning
confidence: 97%
“…Due to the dynamic nature of the system, the boundaries and the fluid-structure interaction forces between the plate and the fluid do not remain constant. Therefore, the need for fluid-structure interaction modelling seems inevitable for the structure and fluid [Gascon-Pérez, 2015;Mnassri and El Baroudi, 2017;Bahaadini and Saidi, 2018;Bahaadini et al, 2018a,b;Saidi et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…Eztensive literatures had studied the characteristic of immersed and submerged plate in fluid Lamb [11] carried out an analytical approach into the investigation of fluidplate coupled system. They determined the natural frequency of clamped circular plate in contact with water using Rayleigh's method, the results were validated later with experimental results of Gascón-Pérez and García-Fogeda [12]. The reviewed of the past studies showed that the analysis of the dynamic behaviour of circular plates resting on Winkler and Pasternak foundations with the aid of differential transformation method has not been investigated.…”
Section: Introductionmentioning
confidence: 99%